2002
DOI: 10.1136/ard.61.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunological, and immunogenetic aspects of autoantibody production against Ro/SSA, La/SSB and their linear epitopes in primary Sjogren's syndrome (pSS): a European multicentre study

Abstract: Objectives: To investigate the clinical and immunogenetic aspects of antibody formation against Ro/SSA and La/SSB as well as their linear B cell epitopes in patients with primary Sjögren's syndrome (pSS) from different European countries. Patients and methods: Ninety patients with pSS from six European centres were studied. Serum samples from all patients were tested in a control laboratory for anti-Ro/SSA and anti-La/SSB autoantibodies by RNA precipitation assay and autoantibodies to the previously reported B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 44 publications
1
40
0
3
Order By: Relevance
“…Some studies also correlated anti-Ro/La antibody positivity to recurrent or permanent parotid gland enlargement [5,22,34] decreased salivary flow [22], more intense symptoms from the eyes, worse Schirmer test and Rose Bengal staining scores [36] and positive salivary gland biopsy [5]. In pSS the degree of labial salivary gland infiltration [37], as well as the development of germinal centre like structures [38] has been associated with the presence of anti-Ro/SSA and anti-La/SSB antibodies.…”
Section: Clinical Implications Of Anti-ro/ssa and Anti-la/ssb In Sjögmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies also correlated anti-Ro/La antibody positivity to recurrent or permanent parotid gland enlargement [5,22,34] decreased salivary flow [22], more intense symptoms from the eyes, worse Schirmer test and Rose Bengal staining scores [36] and positive salivary gland biopsy [5]. In pSS the degree of labial salivary gland infiltration [37], as well as the development of germinal centre like structures [38] has been associated with the presence of anti-Ro/SSA and anti-La/SSB antibodies.…”
Section: Clinical Implications Of Anti-ro/ssa and Anti-la/ssb In Sjögmentioning
confidence: 98%
“…Several studies reported a higher prevalence of extraglandular manifestations in SS patients positive for anti-Ro/La [5,22,34]. In a French cohort of 445 pSS patients anti-Ro/SSA and anti-La/SSB antibodies correlated with a younger age at diagnosis and a higher prevalence of recurrent parotidomegaly, cutaneous vasculitis, Raynaud phenomenon and renal involvement.…”
Section: Clinical Implications Of Anti-ro/ssa and Anti-la/ssb In Sjögmentioning
confidence: 98%
See 1 more Smart Citation
“…The whole ANA group comprises autoantibodies against diverse nuclear components with different clinical impacts [3]. Some of them are rare while others have been found frequently, including SS-A(Ro) and SS-B(La) antibodies that are associated with systemic autoimmune diseases as Sjögren's syndrome, systemic lupus erythematosus and rheumatoid arthritis [4]. Detection of ANA and antibodies to SS-A and SS-B is a possible way to identify persons with a predisposition to rheumatic autoimmune diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…The biological significance of the determination of HLA studies to understand the variability of the inflammatory process can be seen in other diseases; HLA-DRB1 and HLA-DRB3 specificities in sarcoidosis patients identified that the presence of HLA-DRB1*03 favors a course of disease which is associated with Lofgren's syndrome [12]. Also the presence of anti-Ro/SSA and anti-La/SSB autoantibodies was significantly associated with the presence of HLA-DRB1*03 and HLA-DQB1*02 in patients with primary Sjögren's syndrome [13].…”
Section: The Past: Unfulfilled Promisesmentioning
confidence: 86%